Babysitter Finder Mobile Application with Geofencing - Izul Murad, Siti Nursyazwani; Mohd Ghazalli, Hajar Izzati; Rosland, Siti Nurqamarina; Azhari, Amirah Zulaikha (2020)
Babysitter is a person who takes care of children with paid amount of rate and working hour that demanded by babysitter itself. Working parents need babysitters to look after their children while they are working. Finding a babysitter is a tedious work as some parent has their own requirement. Moreover, they had limited time. Other than that, parent usually finds babysitter manually by asking their relatives, neighbor and friends. This may lead to imprecise information about the babysitter. Therefore, a mobile application is developed to solve the problem. This application uses geofencing technology that suit with the problem statement and objectives of the project. Geofence is used to fence babysitter’s location within 500 meters from user. When parent enter in the babysitter’s location, the application will trigger notification that there is a nearby babysitter. Parent also can view babysitter’s profile such as age, contact details, location, availability and price. Thus, parent will get the accurate information about the babysitter since the information directly from the person. As conclusion, every function of the system has been tested and the result of each modules come out as the system expect. The objective of the system successful achieve which the system can pop up notification as indicator that user in the babysitter location. This is proved that the system can detect nearby babysitter location at the user current location. As well as user move out from the babysitter location, system can detect and give notification to user that they already exit from babysitter location